2004
DOI: 10.4049/jimmunol.173.11.6858
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Host Response in Models of Acute HIV Infection

Abstract: HIV infection is characterized by a host response composed of adaptive and innate immunity that partially limits viral replication; however, it ultimately fails in eradicating the virus. To model host gene expression during acute HIV infection, we infected cynomolgus macaques with the SIV/HIV-1 chimeric virus, SHIV89.6P, and profiled gene expression in peripheral blood over a 5-wk period using a high density cDNA microarray. We demonstrate that viral challenge induced a widespread suppression of genes regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 40 publications
8
62
0
Order By: Relevance
“…However, this antiviral response cannot fully control HIV replication. Our data are consistent with previous reports, demonstrating that the innate immunity does sense and respond to HIV, but is inefficient in constraining the virus (13,44,45). Molecular mechanisms permitting HIV to escape from the antiviral IFN response likely contribute to this failure of the innate immune system.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, this antiviral response cannot fully control HIV replication. Our data are consistent with previous reports, demonstrating that the innate immunity does sense and respond to HIV, but is inefficient in constraining the virus (13,44,45). Molecular mechanisms permitting HIV to escape from the antiviral IFN response likely contribute to this failure of the innate immune system.…”
Section: Discussionsupporting
confidence: 82%
“…High-throughput gene expression profiling has also been performed on other cell types, such as monocyte-derived macrophages (7), monocyte-derived immature DCs (8), and peripheral blood from simian-HIV-infected macaques (13). In these systems, up-regulation of ISGs was also found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Gene expression profiling of macaques acutely infected with SIV/HIV-1 chimeric virus (SHIV) demonstrated a differential expression of 10 apoptosis regulators during the first 2 weeks of infection, including TNFRSF6 (tumor necrosis factor receptor superfamily, member 6 (FAS)), BCL2, BCL2L1, DAD1,TIAL1 and PDL2. 13 Accordingly, pathogenic SHIV was shown to induce an accumulation of apoptotic cells during the second week of infection in both lymph nodes and thymus, which colocalized to sites of both virus replication and CD4 T-cell loss. 14 …”
Section: During Acute Infectionmentioning
confidence: 99%
“…Other in vivo reports indicated that elevated IFN-stimulated gene expression was associated with disease progression in HIV-infected patients following cessation of HAART (R A Lempicki et al, unpublished observations), as well as in SIV-infected cynomolgus macaques [19]. Type I interferon produced in lymphoid tissue (LT) of macaques infected with SIV did not inhibit viral replication [20].…”
Section: Interferon-α In Hiv-1 Disease and Therapymentioning
confidence: 99%